Morphological Analysis of The Novel Fatamorgana by Prilly Latuconsina: Morfologi, Afiksasi, Reduplikasi - Fadiah Khoriunnisa Salkeri; Aninditya Sri Nugraheni (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2026)
The problem in this study is how to understand the shape of phonemes in morphological studies. The purpose of this research is to describe the use of morphological vocabulary in the novel Mirage by Prilly Latuconsina. This study uses a qualitative method research approach, namely by analyzing the research object objectively, morphological analysis in the novel Mirage chapter 1 by Prilly Latuconsina. The result was the morphology of a literary work entitled "Mirage". This study covers the forms of affixation and reduplication in the novel Mirage part 1. Based on the results of the analysis of morphological s tudies in the first chapter of the novel Mirage, it can be concluded that there is a form of affixation used in the form of prefixes, namely with the suffix (ber-), (me-), (di-), and (ter-). Suffix affixation forms (-kan), (-an), and (-nya) then in the form of infix affixation there are phonemes with the suffix (-em-), (-el-), and (-er-). The forms of reduplication contained in this novel are total/total reduplication and partial reduplication. In the form of total reduplication analysis, there are seven words, namely the words moments, words, friends, books, novels, animals, and movies. While the partial form of reduplication greetings is only found in two words, namely in the word over time and many times. Keywords: Morphology, Afduction, Reduplication